2004
DOI: 10.1021/nl049951r
|View full text |Cite
|
Sign up to set email alerts
|

Gap-Dependent Optical Coupling of Single “Bowtie” Nanoantennas Resonant in the Visible

Abstract: Metallic "bowtie" nanoantennas consisting of two opposing tip-to-tip Au triangles have been fabricated with triangle lengths of 75 nm and gaps ranging from 16 to 488 nm. For light polarized along the line between the two triangles, the plasmon scattering resonance first blueshifts with increasing gap, and then red-shifts as the particles become more and more uncoupled, while perpendicularly polarized excitation shows little dependence upon gap size. This behavior may be approximately understood in a coupled-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
445
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(469 citation statements)
references
References 17 publications
15
445
1
Order By: Relevance
“…Tailoring and controlling optical near-fields in plasmonic nanostructures facilitate the enhancement of numerous linear and nonlinear optical effects [45,50,51,52,53]. Applications are diverse and include surface enhanced Raman scattering [1,2], second [3,4] and third [5,6] harmonic generation, two-photon photoluminescence [59,60], continuum generation [61] or localized multiphoton photoemission [7,8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tailoring and controlling optical near-fields in plasmonic nanostructures facilitate the enhancement of numerous linear and nonlinear optical effects [45,50,51,52,53]. Applications are diverse and include surface enhanced Raman scattering [1,2], second [3,4] and third [5,6] harmonic generation, two-photon photoluminescence [59,60], continuum generation [61] or localized multiphoton photoemission [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…The optimization of the evaporation conditions improved the surface roughness (measured by the root-mean-squared (RMS) value of the surface height) and enabled the fabrication of high quality nanoantennas. Plasmonic nanostructures offer unique possibilities for enhancing linear and nonlinear optical processes [45,50,51,52,53,6]. Recently, Kim et al [24] reported nanostructure-enhanced high harmonic generation (HHG).…”
Section: Home-built Vacuum Setup For Euv Light Generation and Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…O ptical resonances of metallic nanostructures have shown extraordinary capabilities in manipulating visible light in subdiffraction-limited volumes [1][2][3][4][5][6] . This feature enables high-density information encoding using nanostructures that resonate at different wavelengths, as seen in colour prints with resolutions at the diffraction limit of light 7,8 .…”
mentioning
confidence: 99%
“…Fluorescence from emitters and Raman scattering of a molecule in the vicinity of plasmonic nanoantennas can be substantially enhanced, enabling the detection of species even down to single molecule level. Numerous types of nanoantenna configurations have demonstrated their ability to confine light at nanoscale and strongly enhance local fields, such as bowties [11,12], nanorods [13], nanorings [14,15] and clusters of nanoparticles [16]. However, most of these antennas are limited by the narrow band spectral response because of their dipolar nature, with a typical bandwidth at the order of 100 nm.…”
Section: Introductionmentioning
confidence: 99%